Qualitative meta-synthesis of barriers and facilitators that influence the implementation of community pharmacy services: Perspectives of patients, nurses and general medical practitioners - Hossain, L.; Fernandez-Llimos, F.; Luckett, T.; Moullin, Joanna; Durks, D.; Franco-Trigo, L.; Benrimoj, S.; Sabater-Hernández, D. (BM J Group, 2017)
© Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2017. All rights reserved. No commercial use is permitted unless otherwise expressly granted. Objectives The integration of community pharmacy services (CPSs) into primary care practice can be enhanced by assessing (and further addressing) the elements that enable (ie, facilitators) or hinder (ie, barriers) the implementation of such CPSs. These elements have been widely researched from the perspective of pharmacists but not from the perspectives of other stakeholders who can interact with and influence the implementation of CPSs. The aim of this study was to synthesise the literature on patients', general practitioners' (GPs) and nurses' perspectives of CPSs to identify barriers and facilitators to their implementation in Australia. Methods A meta-synthesis of qualitative studies was performed. A systematic search in PubMed, Scopus and Informit was conducted to identify studies that explored patients', GPs' or nurses' views about CPSs in Australia. Thematic synthesis was performed to identify elements influencing CPS implementation, which were further classified using an ecological approach. Results Twenty-nine articles were included in the review, addressing 63 elements influencing CPS implementation. Elements were identified as a barrier, facilitator or both and were related to four ecological levels: individual patient (n=14), interpersonal (n=24), organisational (n=16) and community and healthcare system (n=9). It was found that patients, nurses and GPs identified elements reported in previous pharmacist-informed studies, such as pharmacist's training/education or financial remuneration, but also new elements, such as patients' capability to follow service's procedures, the relationships between GP and pharmacy professional bodies or the availability of multidisciplinary training/education. Conclusions Patients, GPs and nurses can describe a large number of elements influencing CPS implementation. These elements can be combined with previous findings in pharmacists-informed studies to produce a comprehensive framework to assess barriers and facilitators to CPS implementation. This framework can be used by pharmacy service planners and policy makers to improve the analysis of the contexts in which CPSs are implemented.